Paratonia, Gegenhalten and psychomotor hypertonia: back to the roots - Foucher, Jack R.; Dormegny-Jeanjean, Ludovic C.; Bartsch, Andreas J.; Humbert, Ilia; de Billy, Clément C.; Obrecht, Alexandre; Mainberger, Olivier; Clauss, Julie M. E.; Waddington, John L.; Wolf, Robert Christian; Hirjak, Dusan; Morra, Carlos; et al. (Schizophrenia research, 2024)
In the first half of the 20th century, well before the antipsychotic era, paratonia, Gegenhalten and psychomotor hypertonia were described as new forms of hypertonia intrinsic to particular psychoses and catatonic disorders. A series of astute clinical observations and experiments supported their independence from rigidity seen in Parkinson's disease. After World War II, motor disorders went out of fashion in psychiatry, with drug-induced parkinsonism becoming the prevailing explanation for all involuntary resistance to passive motion. With the ‘forgetting’ of paratonia and Gegenhalten, parkinsonism became the prevailing reading grid, such that the rediscovery of hypertonia in antipsychotic-naive patients at the turn of the 21st century is currently referred to as “spontaneous parkinsonism”, implicitly suggesting intrinsic and drug-induced forms to be the same. Classical descriptive psychopathology gives a more nuanced view in suggesting two non-parkinsonian hypertonias: (i) locomotor hypertonia corresponds to Ernest Dupré's paratonia and Karl Kleist's reactive Gegenhalten; it is a dys-relaxation phenomenon that often needs to be activated. (ii) Psychomotor hypertonia is experienced as an admixture of assistance and resistance that partially overlaps with Kleist's spontaneous Gegenhalten, but was convincingly isolated by Henri Claude and Henri Baruk thanks to electromyogram recordings; psychomotor hypertonia is underpinned by “anticipatory contractions” of cortical origin, occurrence of which in phase or antiphase with the movement accounted for facilitation or opposition to passive motions. This century-old knowledge is not only of historical interest. Some results have recently been replicated in dementia and as now known to involve specific premotor systems.